Relevance of the Communicative Method of Teaching Language - Yakubov Abdurasul Soatovich; Aminova Rokhila Khamidovna (Research Parks Publishers, 2021)
This article examines the current stage of development of methods of teaching foreign languages in the national audience. When using it, the main attention is paid to the assimilation of the language system; in university practice, the learning process is identified with the study of grammar, sometimes with the mechanical memorization of grammatical rules, definitions, paradigms